THE INCREASING STUDENTS' BIOLOGY CONCEPT MASTERY THROUGH THE APPLICATION OF THE GUIDED INQUIRY LEARNING MODEL - Indah Panca Pujiastuti (Universitas Sulawesi Barat, 2022)
Mastery of the concept is one indicator of the success of learning. Facts based on observations made by researchers in class X at the State Madrasah Aliyah in Malang, East Java show that students' mastery of concepts is still not well developed. This can be seen from the average daily test score, which is more than 70% of students who score below the Minimum School Learning Criteria, namely 78. This problem certainly requires a solution in the form of applying appropriate learning models, such as guided inquiry. The purpose of this study was to improve students' mastery of concepts through the guided inquiry learning model. The approach in this research is a qualitative approach which is carried out through Classroom Action Research with 2 cycles. The cycle in this study consisted of 4 stages, namely planning, implementing, observing, and reflecting. The subjects of this study were 36 students. Students' mastery of concepts in this study was measured through essay test questions. Indicators of student mastery of concepts refer to the revision of Bloom's Taxonomy which includes remembering, understanding, applying, analyzing, evaluating, and creating. Data analysis of mastery of the concept using gain score analysis. The results of this study were an increase in mastery of the concept from cycle I, namely 64 to 82 in cycle II. The conclusion that can be drawn from this study is that there is an increase in students' mastery of concepts from cycle I to cycle II.